Sistem Informasi Absensi Perangkat Desa di Kecamatan Bengkayang - Rupina Rupina; Candra Gudiato (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Attendance and punctuality of employee attendance are often used as one indicators in employee performance assessment.Employee absenteeism has a big impact on work productivity in achieving company goals, especially in government agencies related to community services. Regarding the village apparatus in Bengkayang District, it is ONE of the government agencies that still carries out the attendance process manually so that data collection on attendance hours, entry hours, departure times, recapitulation of employee absences requires a relatively long time in the calculation and data search process. This manual attendance process is prone to causing incidents loss of data can affect the credibility of the data used to make employee absence reports. Based on these problems, something is needed employee attendance information system to manage data related to employee absences. The Employee Attendance Information System in this research was built using a qualitative method, where this method consists of the stages of problem analysis, system requirements, system requirements analysis, and system design. By implementing the village apparatus attendance information system in Bengkayang sub-district, it is hoped that it can help in managing employee attendance data and improve agency performance. Send feedback Side panels History Saved